A Compact Design of Transparent Microstrip Antenna For Wireless Car-to-Car Communication System - Rahayu, Yusnita; D.A, Raja; B. P, Yoga (International Journal of Electrical, Energy and Power System Engineering, 2019)
In this paper, a compact design of transparent rectangular microstrip antenna with a slotted ground plane has been designed and evaluated to support Intelligent Transportation System (ITS). The proposed antenna consists of a single element using transparent conductive film AgHT-4 layered on a plain glass substrate, fed by a single 50 Ω SMA port. The antenna is working on 5.9 GHz based on IEEE 802.11p for Wireless Access in Vehicular Environment (WAVE) Standard. The design concept is to have arc shape slot out of the ground plane of a microstrip patch antenna to enable wideband frequency. The proposed antenna provides ultra wide impedance bandwidth around 750 MHz (5.48-6.23 GHz) at a center frequency of 5.9 GHz. The proposed transparent antenna has a directivity gain of 6.266 dBi.